History of the International Organization for Biological Control Global Working Group on Mass Rearing and Quality Assurance. Issue 2 (7th March 2019) - Leppla, Norman C; Clercq, Patrick De
Abstract: The International Organization for Biological Control Global Working Group on Mass Rearing and Quality Assurance (MRQA) was established in 1980 as the Working Group on Quality Control (WGQC) to assure success of insect mass rearing for pest management that was being developed in the 1950s and 1960s. Due mostly to the efforts of WGQC, quality control became institutionalized in several insect mass rearing facilities during the 1980s. After addressing autocidal control programs, the WGQC concentrated on entomophagous insects, especially testing the quality of commercial biological control products. Universal Implementation of Quality Control for Mass-Reared Arthropods was finally achieved in the 1990s, having encompassed all aspects from insect production to field application and evaluation. This increased scope prompted a name change from WGQC to Arthropod Mass Rearing and Quality Control (AMRQC). Subsequently, the scope of the Working Group was expanded again and it was renamed MRQA to include a range of applications for mass-reared beneficial invertebrates. The geographic range of MRQA recently was extended beyond North and South America and Europe to include India. This expansion continued as insects for food and feed, networking and instruction, and legal and ethical issues were added to the most recent workshop held in Mexico. Thus, the MRQA continues to evolve as additional invertebrate organisms are mass produced for both established and novel applications.